2007
DOI: 10.4049/jimmunol.178.1.397
|View full text |Cite
|
Sign up to set email alerts
|

Lamprey TLRs with Properties Distinct from Those of the Variable Lymphocyte Receptors

Abstract: Fish express mammalian-type (M-type) TLRs consisting of leucine-rich repeats (LRRs) and Toll-IL-1R (TIR) homology domain for immunity, whereas invertebrates in deuterostomes appear to have no orthologs of M-type TLRs. Lampetra japonica (lamprey) belongs to the lowest class of vertebrates with little information about its TLRs. We have identified two cDNA sequences of putative TLRs in the lamprey (laTLRs) that contain LRRs and TIR domains. The two laTLRs were 56% homologous to each other, and their TIRs were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 44 publications
(55 reference statements)
2
36
0
Order By: Relevance
“…In contrast, fish and xenopus have unique TLR2 subfamilies of TLR1, TLR2 and TLR14 (2,8,16). Even the lamprey appears to have the TLR2 subfamily (17).…”
Section: Results and Dicussionmentioning
confidence: 99%
“…In contrast, fish and xenopus have unique TLR2 subfamilies of TLR1, TLR2 and TLR14 (2,8,16). Even the lamprey appears to have the TLR2 subfamily (17).…”
Section: Results and Dicussionmentioning
confidence: 99%
“…In mammal, TLR2 is involved in the recognition of a wide range of PAMPs, such as lipopeptides from bacteria, and peptidoglycan and lipoteichoic acid from Gram-positive bacteria, through the interaction with other receptors, such as TLR1 and TLR6, and also CD36 and CD14 (Kawai and Akira, 2010). In teleost fish, TLR6 and TLR10 are not identified, and TLR4 is only found in pufferfish and zebrafish as well as in lamprey (Lampetra japonica) (Ishii et al, 2007). But unlike in mammal, TLR4 in zebrafish does not recognize LPS (Sepulcre et al, 2009); and recent research has shown that TLR2 in fish may be incorporated with PGRP (Chang and Nie, 2008), and can indeed bind lipoteichoic acid and peptidoglycan, as mammalian TLR2 (Ribeiro et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Anchoring to the plasma membrane might be important to keep the pre- EFR-FLS2 Chimeras-To study the elf binding properties and EFR functionality, we substituted parts of the receptor by corresponding parts of the closely related LRR receptor kinase FLS2. Chimeric constructions with domain swaps between different receptors have previously been used to investigate specificity of ligand interaction and signal output of Toll-like receptors in humans and animals (29,30). In plants, a much-noticed first example was reported for a chimera of the pattern recognition receptor XA21 from rice and the brassinolide receptor BRI1 from A. thaliana (31).…”
Section: Efr Ectodomain As Interaction Site For the Elf Ligands-map-mentioning
confidence: 99%